The knowledge, attitude and practices regarding commonly occurring mosquito borne diseases among people in catering area of urban health and training centre - Sharma, Ashutosh; Gupta, Vinita; Khandelwal, Ashish (International Journal Of Community Medicine And Public Health, 2017)
Background: Mosquito borne diseases are major public health problems and emerging diseases in India. These are endemic in some parts of country with periodic outbreaks. South East Rajasthan is one of the region which showed such major outbreak during post monsoon period. Methods: This cross-sectional study was carried out in the month of September to November 2016 in field practice area of UTHC Mahaveer Nagar, Govt. Medical College, Kota. 1083 houses were selected for the study by systemic sampling and pre tested and semi structured questionnaire were filled by adult member of family. Data was analysed in Microsoft Excel 2010 & SPSS ver16. Results: Out of 966 respondents 88.4% were aware about mosquito borne diseases. Fever as chief complaint was known to 97.16%. Majority of them believe that mosquito breeds in dirty water. Television and newspaper are main source of information on mosquito borne disease. Mosquito mat/coil/liquid vaporizer is used by most of them during night time only. Most of respondents neither check cooler for mosquito larvae nor changed water in coolers within a week. Conclusions: Study recommends increasing the knowledge and application of preventive measures by massive awareness campaign before monsoon so to reduce the health care burden from mosquito borne diseases.